Beyond indigestion: emerging roles for lysosome-based signaling in human disease. (August 2015) - Ferguson, Shawn M
Highlights: Lysosomes integrate multiple signals required for mTORC1 signaling. Lysosomal signals regulate gene expression through MiT-TFE transcription factors. Multiple diseases arise from mutations in lysosomal signaling protein genes. Abstract : Lysosomes are becoming increasingly recognized as a hub that integrates diverse signals in order to control multiple aspects of cell physiology. This is illustrated by the discovery of a growing number of lysosome-localized proteins that respond to changes in growth factor and nutrient availability to regulate mTORC1 signaling as well as the identification of MiT/TFE transcription factors (MITF, TFEB and TFE3) as proteins that shuttle between lysosomes and the nucleus to elicit a transcriptional response to ongoing changes in lysosome status. These findings have been paralleled by advances in human genetics that connect mutations in genes involved in lysosomal signaling to a broad range of human illnesses ranging from cancer to neurological disease. This review summarizes these new discoveries at the interface between lysosome cell biology and human disease.